Riots : Prevention and Control - Ghosh, S.K.; Sarkar,A.K. (Fwd.) (Calcutta, 1971)
The present book deals with one of such problems, namely, riots which unfortunately appear in recent times to have been of far too frequent occurrence. This particular problem has many facets, such as, communal riots, labour troubles and student disorders. Each facet has its own peculiar characteristic and derives its origin from apparently different causes. The method of dealing with them has necessarily to be different. The author, who has had a very wide experience in the matter, has dealt with these several facets in separate compartments : the causes which have given rise to this unfortunate recurring phenomenon have been mentioned by him so far as he has discovered them in the discharge of his duties and his studies connected with them, but the main object of his work is not to suggest means to eradicate these causes. The treatise as its title states, is principally concerned with prevention and control of riots.
Keywords: Riots India